(untitled) (Global Journal of Human-Social Science, 2018)
Wh ile conducting the research in Emotional Intelligence about the human resource in educational institutes i e secondary school teachers the researcher was always curious to know about what are those teachers remembered by today s teachers And what can be the reasons for recalling only those particular teachers While conducting EQ awareness programs and S EI Social Emotional Intelligence Assessment the researcher organized various interventions between Pre and Post Training Assessments for Teachers The base of developing and designing the modules was Pre Training Assessments Where the researcher obser ved that teachers are struggling to achieve SEI Compe- tencies namely Navigating Emotions Empathy Recognizing Patterns and Pursue Noble Goal She always wanted to know what is the purpose teachers have for their profession When she asked some questions while interviewing them in groups and also then they were writing individually about their teachers who taught them in their schools when they were learning in their childhood most of the teachers wrote and responded that they remember joyful an d understanding teachers As an EQ researcher especially in the field of HRM Impact of teachers Emotional Intelligence on student s performance this data found very interesting and important to her This research paper will put forth the light upon ho w the teachers recently teaching in the schools when the researcher gave them an option to choose a teacher to follow in their life now they want to remember and choose those who are joyful understanding happy helpful careful smiling giving creating examples and so on